"Sacred Connections: Nuns, Goddesses, and Yakshinies in Jain Philosophy" (International Journal of Food and Nutritional Sciences, 2019)
This research article delves into the intricate relationships between nuns, goddesses, andYakshinies within Jain Philosophy, offering a nuanced exploration of their significance inJainism. Through meticulous analysis of historical texts, archaeological findings, and insightsfrom renowned historians, this study illuminates the profound spiritual connections and theirimplications for understanding the role of femininity and divine entities in Jain philosophicalthought.